Identification of Plant Traits for Characterization of Early Maturing Upland Cotton Varieties - Baloch, Muhammad Jurial; Veesar, Nasreen Fatima (Biological Sciences - PJSIR, 2007)
Thirteen upland cotton varieties with morphologically distinguished plant traits were evaluated so, as to characterize early maturi ng cotton. According to ANOVA test , the varieties differed significantly for all the traits studied . The varieties, in days taken to set first flower varied from 4 1 .0 to 48.0; sympodial branch node numbers 5 .5 to 9.0; I " effective bo ll setti ng branch n umber 6.3 to I 0.3; sympodi al branch len gth 14.2 to 35.7 cm; bo ll open i ng 53.0 to 81.0%; boll weight 2.7 to 4.5 g, and seed cotton yield I 26.0 to 196.3 g. Tt w as observed that most of the pl ant trai ts simultaneously favoured the varieties in th ei r characterizati on for earl i n ess. Thu s as compared to l ate m aturing vari et i es, ear l y v arieties took mi nimu m of 41 .0 days to set fi rst flower, produced l ower sympodial branches at 5.5 to 6.51h n odes; set fi rst effective bo ll at 6.3 to 7.5'h nodes; prod uced shorter sympod i al bran ch es of 14.2 to 21.6 cm; opened 75.0 to 81.0% of boll s at 120 days after plantin g, gave medi um bolls of 3.0 to 3.5 g. Accordi ng to short season's classification , the varieties which opened 75 to 81% of their bolls were if picked after 145 days, the boll openi ng percent may h ave reached about 95%. Thus such varietie s could be considered as earl y maturing on es. In presen t studies, va ri eties CIM-511 , CTM-506, NIAB-999, BH- 147, CRIS-467, CRIS- 168 and CRIS-342 can be characterized as early maturi n g cotton . Si gni ficant correlation coeffic i ent (r) values between earli n ess plant tra its further su ggested that selection of one trai t for earl i ness can indirectl y but simultaneously i mprove another trait rel ated to earliness.